АНАЛІЗ НАУКОМЕТРИЧНИХ ПОКАЗНИКІВ ЖУРНАЛУ «ТЕХНІЧНА ЕЛЕКТРОДИНАМІКА» 2018–2020 рр. - Городжа, Л.В. (Інститут електродинаміки НАН України, Київ, 2021)
The directions of development of the journal "Technical Electrodynamics" in recent years are considered, its main scientometric indicators according to Scopus data for 2020 are analyzed, their comparison with the indicators of the previous two years is made. It is noted that indicators such as SJR, percentile, international cooperation decreased, the Hirsch index and quartiles remained at the same level. Ways to improve the performance of the journal are suggested. References 6.